1999
DOI: 10.1093/hmg/8.13.2473
|View full text |Cite
|
Sign up to set email alerts
|

Very Large (CAG)n DNA Repeat Expansions in the Sperm of Two Spinocerebellar Ataxia Type 7 Males

Abstract: Genetic anticipation, i.e. increasing disease severity and decreasing age of onset from one generation to the next, is observed in a number of diseases, including myotonic dystrophy type 1, Huntington's disease and several of the spinocerebellar ataxias. All of these disorders are associated with the expansion of a trinucleotide repeat and array length is positively correlated with disease severity and inversely correlated with the age of onset. The expanded repeat is highly unstable and continues to expand fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 33 publications
4
34
0
2
Order By: Relevance
“…A later study of 182 families from two particular Long QT syndromes did not find the same distortion to the expected 50:50 Mendelian transmission. 10 Diseases caused by expansion of CAG repeats, such as Machado-Joseph disease 11,12 and spinocerebellar ataxia 7 13 are suggested to show a prevalence of transmission of the mutant allele, but again have conflicting reports. Investigating transmission at two CAG disease repeat loci, TRD was noted in male meioses in live-born offspring 11 and in sperm typing from MJD patients 14 and preferentially transmitted to live-born offspring by female carriers.…”
Section: Introductionmentioning
confidence: 99%
“…A later study of 182 families from two particular Long QT syndromes did not find the same distortion to the expected 50:50 Mendelian transmission. 10 Diseases caused by expansion of CAG repeats, such as Machado-Joseph disease 11,12 and spinocerebellar ataxia 7 13 are suggested to show a prevalence of transmission of the mutant allele, but again have conflicting reports. Investigating transmission at two CAG disease repeat loci, TRD was noted in male meioses in live-born offspring 11 and in sperm typing from MJD patients 14 and preferentially transmitted to live-born offspring by female carriers.…”
Section: Introductionmentioning
confidence: 99%
“…A high level of mosaicism was commonly observed in sperm, with this mosaicism overlapping the sizes inherited by the offspring, suggesting that intergenerational instability results mainly from germinal instability in the father (8,12,25,34,38,52,53). However, several studies, including one on fragile X fetuses and one on transmission in Friedreich ataxia families, suggested that intergenerational length changes could also involve a postzygotic instability event (13,14,37).…”
mentioning
confidence: 99%
“…CAG repeat instability has previously been described in a number of polyQ diseases as germ-line instability or intergenerational variations in repeat size. 4,5,7,9,10 However, to our knowledge, analyses of germ-line instability have not been investigated in SCA2. Out of 18 single spermatozoa with the expanded ATXN2 allele, 4 (22%) showed an expansion beyond the 45 CAG repeats detected in somatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, in SCA1 and SCA3 the longest gains reported were by 12 and 24 CAG repeats, 7,11,12 respectively, whereas much longer gains have been reported for SCA7 and DRPLA. 9,10 Exactly why CAG repeats in some genes are gaining more repeats than others remains obscure, but it seems that within a given disease longer repeats tend to be more unstable, as do pure CAG repeats, compared with repeats interrupted by CAA codons. 2,3 The extreme expansion observed in the girl was surprising, given the fact that her father's pathogenic allele of 45 glutamine codons was interrupted by a CAA codon at position 37.…”
Section: Discussionmentioning
confidence: 99%